Mental Health in Higher Education: A Comparative Stress Risk Assessment at an Open Distance Learning University in South Africa - Poalses, Jacolize; Bezuidenhout, Adéle (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Universities depend on committed efforts of all staff members to function effectively. However, where occupational demands outweigh occupational resources, challenging work becomes stressful, followed by an exhausted, disengaged workforce. It is unlikely that disengaged university staff will provide adequate care and service to geographically distant and psychologically isolated learners. As students rely heavily on the support of both administrative staff, as well as academic staff, to manage their learning experience, the work stress experienced by both groups deserves research attention. This study employed a comparative mixed method design, including administrative and academic staff from an Open Distance Learning university in South Africa using the Job Demands-Resources measurement instrument. Findings established from 294 university staff members elucidated staff members’ experience of work stress within a mega-distance learning university in the developing world. Mindfulness about the stressors that influence university personnel can inform strategic interventions required to alleviate distress for each employment category.